Królestwo Boże (Józefa Czapskiego podróż do Hiszpanii w roku 1930) - Franaszek, Andrzej (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
The author of the article describes a trip to Spain made by Józef Czapski in 1930. This outstanding painter and essayist, witness to the Katyń massacre, co-creator of the Parisian magazine "Kultura" [Culture] and Polish intellectual life in exile, at the time of visiting Madrid and its nearby areas for nearly two months was still a young artist, looking for the painting poetics closest to his soul. The visits to the Prado brought him two great discoveries: the works of El Greco and Goya. For Czapski, El Greco is a captivating example of religious painting and simultaneously - fidelity to the vision, the way of seeing the world. Goya fascinated Czapski with the thematic and stylistic range of his art - from “official” court portraits to dramatic records of nearly surreal visions, reflecting the artist’s fundamental belief in human depravity. The trip to Spain also had another meaning for Czapski - it was in a way a journey in the footsteps of St. Teresa of Avila, broadly: a reflection on the role of mystical experience in the spiritual life of man. From these two perspectives: artistic and religious, the encounter with the Spanish culture appears to be one of the more important and fateful episodes in the biography of Józef Czapski.